Biosimilar insulins: What do you need to know?. Issue 1 (2nd January 2017) - James, June; Pollom, Robyn K.; Hadjiyianni, Irene; Buchholz, Gabriele; Reed, Beverly L.
Abstract : Biologics are large, complex molecules derived from living organisms and include hormones, such as insulin. Biologics possessing an identical amino acid structure, and similar efficacy and safety to an approved reference product are called biosimilars. The first biosimilar insulin was approved in the European Union in 2014 and more are expected to come to market. Patient education for biosimilar insulins is the same as for other insulins, but additional factors for patients changing their insulin should be considered. This article is a resource for healthcare professionals who treat patients with diabetes and support them in making important treatment decisions.